A Quantitative Study on Culinary Tourism: The Effect of Service Quality on Purchase Decision Through Trust and Word of Mouth - Andika Isma; Andi Naila Quin Azisah Alisyahbana; Rahmawati Rahmawati; Rachmawati Kadir (Politeknik Pariwisata Makassar, 2024)
This study aims to investigate the effect of service quality on purchasing decisions on culinary tourism, by considering the role of Trust and Word of Mouth as mediating variables. This study uses a quantitative approach of descriptive research and explanatory research that describes the relationship between variables with a population of all visitors to Makassar City's typical restaurants or stalls which are the main destinations for culinary tourism. Data analysis in this study PLS-SEM Warp Analysis and Sobel Test. The results showed that: 1) Directly Service Quality, Trust, Word of Mouth have a significant effect on Purchase Decision. 2) Indirectly Service Quality, Trust, Word of Mouth have a significant effect on Entreprenurial Intention. Based on the results of this study, it is known that consumers feel that joining a community or group can fulfill the information needs needed related to culinary tourism, then with the spread of word of mouth and good trust, it will increase the reputation of a place of Makassar City Restaurant or Warung which is the target of culinary tourists so that it needs to be given more attention in terms of service quality.